Performance of Different Organic Fertilizers on Wheat Yield at Tikapur, Kailali - Sharma, Raksha; Tiwari, Shreya; Lamichhane, Sima; Subedi, Saurab (KMC Journal, 2024)
A field experiment was carried out to investigate the effect of different organic materials alone and in combination on the yield of wheat variety Aditya during November 2021- April 2022 in the Agronomy Field of Far Western University, Tikapur, Kailali. The study was carried out with 7 treatments viz. Farmyard manure (FYM), Vermicompost (V), Trichoderma viridae (T), FYM + V (FV), FYM + T(FT), FYM + V + T(FVT) and Control (without any organic matter) and laid out in Randomized Complete Block design with three replications. Chemical fertilizers were not used in the study. The result showed significantly higher number of effective tillers, thousand grain weight and grain yield in the treatment FVT as compared to other organic fertilizers and their combinations. But plant height was found to be the highest in FT followed by FYM. An increase of 16% and 36.29% grain yield was recorded in FVT over FT and the control respectively. Wheat grain yield from FV (2.28 t/ha) and FT (2.08 t/ha) were statistically greater than FYM or Vermicompost when applied alone. Application of Vermicompost and VT had relatively lower influence on yield attributes and yield as compared to FYM and FT. However, all the treatments were superior over the control in terms of all the yield and yield attributing traits.